Multilateral negotiations in foreign investment - Ruiz Castro, David Orlando (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2016)
Direct foreign investment is one of the most important economic variables in the world. Aspects related to international investment agreements are reaching an outstanding place in economic international diplomacy. Nowadays, in the multilateral level there is not an agreement regarding investment and therefore this study is focused on this particular type of agreement. In order to reach this objective this study shows, first of all, how different attempts have been developed to get a multicultural a agreement regarding investment, and to refuse the general opinion that says that exponential growth of foreign investment flows in recent years has given impulse to launch a multilateral investment agreement. Secondly, this study discusses about regulations related to foreign investment under current WTO regulations, such as investment, measure agreements, and service agreement. Then, it analyzes what has happened inside the WTO from the creation of the investment team at the Singapore Conference to the failed Conference in Cancun. Finally, it analyzes the main arguments against the multilateral agreement and the effects of future possible multilateral negotiations in investment and it ends with some recommendations and conclusions.